Exploring obscenity in Nigerian Afro-pop music: A sociocultural analysis of Yoruba youth and social norms - Oluwatobi Emmanuel Egbowon; Dilan Çiftçi; Ibrahim Adeshola (PLoS ONE, 2026)
Nigerian Afro-pop music is a popular genre that significantly influences Nigerian society and beyond. While Afro-pop promotes Nigerian culture globally, critics argue that its explicit lyrics and provocative music videos negatively impact young individuals, promoting materialism, sexual promiscuity, and drug use. This research focuses on the cultural implications of “vulgar” Afro-pop music among Yoruba youth in Nigeria. The study employs a quantitative analysis of 295 responses to explore the respondents’ perspectives on offensive content in Nigerian Afro-pop music. The findings highlight music’s potential positive and destructive influences on youth and emphasize the need for regulatory bodies to scrutinize music content before distribution.